SUCCESSFUL MANAGEMENT OF HYDROAMNION IN A MURRAH BUFFALO - MEHRA, UMED SINGH; DUTT, RAVI; SEEMA, (The Indian Journal of Animal Reproduction, 2023)
This communication reports a case of hydroamnion accompanying with fetal anomaly of maxilla and mandibleand knuckling of both forelimbs in a full term Murrah buffalo. The defective fetus was delivered successfully withslight mutation without any post-partum complication to the dam.
Keywords: Hydroamnion; Anomaly; Maxilla; Mandible; Knuckling; Buffalo